Unmasking privacy apprehension: A bibliometric review of mobile sharing economy applications - Thuy-Dzung T. Pham; Fang-Yi Lo; Kun-Huang Huarng (Journal of Innovation & Knowledge)
The emergence of mobile applications (apps) that utilize sharing economy concepts has revolutionized multiple industries, including transportation, accommodation, healthcare, and other sectors. With the nature of massive data collection and sharing policies, these platforms create serious privacy concerns for their users, even though they enhance existing services and enable new economic potential. This research identifies the key contributors and knowledge concerning privacy apprehensions and mobile sharing economy apps. We analyze downloaded bibliographic data from 201 papers from the Scopus database and present the main contributors in the field based on criteria such as journal, article, author, institution, and country. We further employ keyword co-occurrence and thematic mapping techniques to create a scientific map that reveals three distinct groups (clusters) and pinpoints the prominent papers for each cluster. This paper offers valuable insights into the literature's current progress and points out potential directions for future research in terms of privacy concerns in mobile sharing economy apps.